Enhancing proper use of Computer and Internet access by Academics in - (Ph. D), Nkoyo Edem (IJRDO -Journal of Computer Science Engineering, 2016)
The paper reports the extent of use of the computer and access to the internet byacademic staff in selected Nigerian Universities in South- South zone. Most academic staffin Nigerian Universities are aware of the resources of the Internet, but use them relativelyinfrequently. 50.8% and 53.0% use the computer and access internet “occasionally”. Themain reasons for this are lack of access to them and lack of proper training. Even thoughWorld Wide Web (www) is the most popular resource for teaching and research, its use isstill very low due to lack of proper searching skills to retrieve current information. There istherefore the need to use the proper search engines for internet search. Findings showedthat 337(81.2%) use search engines without the knowledge of proper metadata searchkeywords, 42(10.0%) use search engines with proper methadata search keywords, whileother academic staff uses Web Directories 36 (8.8%). Recommendations were made toinclude intensive in –house computer trainings and internet access in various faculties inthe institution with emphasis proper skills on internet use to access published researchworks and current information materials as well as enhance their capabilities in electronicresource usage.